2016
DOI: 10.1121/1.4946897
|View full text |Cite
|
Sign up to set email alerts
|

Auditory localization by subjects with unilateral tinnitus

Abstract: Tinnitus is associated with changes in neural activity. How such alterations impact the localization ability of subjects with tinnitus remains largely unexplored. In this study, subjects with self-reported unilateral tinnitus were compared to subjects with matching hearing loss at high frequencies and to normal-hearing subjects in horizontal and vertical plane localization tasks. Subjects were asked to localize a pink noise source either alone or over background noise. Results showed some degree of difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 43 publications
2
21
2
Order By: Relevance
“…The phenomenon is continuously gaining relevance as it coincides with a steadily aging demographic (Hoffman & Reed, 2004) and concomitant age-related hearing loss (presbycusis; Ferreira, Ramos Júnior, & Mendes, 2009), noisy occupational or leisure time environments (Sanchez et al., 2016; Shargorodsky, Curhan, & Farwell, 2010), and stress (Mazurek, Haupt, & Olze, 2012). Moreover, tinnitus is not only related to altered auditory functions like speech perception (Ivansic et al., 2017; Jagoda et al., 2018), sound source localization (Hyvärinen, Mendonça, Santala, Pulkki, & Aarnisalo, 2016), auditory attention (Cuny, Norena, El Massioui, & Chéry-Croze, 2004), and emotional attention processes (Trevis, McLachlan, & Wilson, 2016), but also to affective disorders like depression or anxiety (Langguth, 2012), insomnia (Croenlein et al., 2016), and lowered quality of life (Nondahl et al., 2007; Weidt et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon is continuously gaining relevance as it coincides with a steadily aging demographic (Hoffman & Reed, 2004) and concomitant age-related hearing loss (presbycusis; Ferreira, Ramos Júnior, & Mendes, 2009), noisy occupational or leisure time environments (Sanchez et al., 2016; Shargorodsky, Curhan, & Farwell, 2010), and stress (Mazurek, Haupt, & Olze, 2012). Moreover, tinnitus is not only related to altered auditory functions like speech perception (Ivansic et al., 2017; Jagoda et al., 2018), sound source localization (Hyvärinen, Mendonça, Santala, Pulkki, & Aarnisalo, 2016), auditory attention (Cuny, Norena, El Massioui, & Chéry-Croze, 2004), and emotional attention processes (Trevis, McLachlan, & Wilson, 2016), but also to affective disorders like depression or anxiety (Langguth, 2012), insomnia (Croenlein et al., 2016), and lowered quality of life (Nondahl et al., 2007; Weidt et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…With a steadily aging demographic, tinnitus is becoming increasingly prevalent and relevant (Hoffman and Reed, 2004; Nondahl et al, 2012). Besides the tantalizing phantom sound or comorbidities like depression, stress and anxiety (Langguth et al, 2013), tinnitus also impacts daily life functions in healthy aging as impaired hearing, sound localization and speech perception can lower the quality of life in tinnitus sufferers (Moon et al, 2015; Gilles et al, 2016; Hyvärinen et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…In other words, HL seems to weaken the auditory processing capabilities of subjects with tinnitus. Hyvärinen et al (2016) found that tinnitus may degrade auditory localization ability, although this effect can also be due to the associated levels of HL. And thirdly, we have not found differences between the average THI score in patients with or without HL (see Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Newman et al (1994) investigated the relationship between psychoacoustic judgements, speech understanding ability and self-perceived handicap in tinnitus and hearing impaired subjects. Hyvärinen et al (2016) reported that tinnitus may degrade auditory localization ability, although this effect is, for the most part, due to the associated levels of HL. Gilles et al (2016) showed that young people with noise induced tinnitus, but normal hearing thresholds, proved impaired speech-in-noise performance.…”
Section: Discussionmentioning
confidence: 99%